Good Corporate Governance Practices in the Management of Regional Public Companies Wai Tipalayo Polewali Mandar Regency - Achmad Fauzi Kusmin; Aco Nata Saputra; Andi Nur Fiqhi Utami; Citra N Fariaty; Muhammad Tanzil Aziz Rahimallah (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles in the management of the Regional Public Company Wai Tipalayo, located in Polewali Mandar Regency. As a public water utility, this regional public plays a vital role in fulfilling basic community needs while contributing to regional original income. Employing a qualitative approach with a phenomenological method, this research explores how the five core principles of GCG transparency, accountability, responsibility, independence, and fairness are applied in organizational governance. Data collection was conducted through direct observation, in-depth interviews with key stakeholders (including directors, managers, and customers), and document analysis. The findings reveal that transparency is implemented primarily through digital platforms such as social media and the company's official website, although financial transparency remains limited to internal stakeholders and regional authorities. Accountability is evidenced by clearly defined job descriptions and routine performance evaluations. The principle of responsibility is reflected in the company's commitment to environmental sustainability and social service to the community. Independence is demonstrated by the company's ability to self-finance operational costs without external political interference. Moreover, fairness is upheld through equitable recruitment practices and equal treatment of employees regardless of their employment status. Overall, the study concludes that consistent application of GCG principles enhances organizational performance and public trust in Wai Tipalayo’s Regional Public Company. However, greater efforts are still required to expand financial transparency and strengthen external collaboration to support sustainable corporate governance.